1998
DOI: 10.1093/oxfordjournals.aje.a009503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity on Preterm Birth

Abstract: The authors conducted a cohort study of low income women to determine the effect of physical activity on the risk of preterm birth. Women were sampled prenatally from four clinic sites and were scheduled for delivery at the University of Maryland Medical Systems (UMMS). Women who delivered infants at UMMS but who had received no prenatal care were also eligible. Preterm delivery was defined as a delivery prior to 37 completed weeks gestation. After adjusting for confounders, the odds of preterm delivery were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
12

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 0 publications
3
66
0
12
Order By: Relevance
“…Therefore, 37 eligible studies (7 case control studies, 18 cohort studies, and 12 interventional studies) were included in the meta-analysis. All the included 25 observational studies (7 case-control studies and 18 cohort studies) were rated as either high18 or moderate91920212223242526272829303132333435363738394041 quality (see Supplemental Tables S1 and S2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 37 eligible studies (7 case control studies, 18 cohort studies, and 12 interventional studies) were included in the meta-analysis. All the included 25 observational studies (7 case-control studies and 18 cohort studies) were rated as either high18 or moderate91920212223242526272829303132333435363738394041 quality (see Supplemental Tables S1 and S2). …”
Section: Resultsmentioning
confidence: 99%
“…It may not be appropriate to combine all domains of PA into a single score and link it to health endpoints including PTB because different domains of PA may have different health impacts. For instance, one study9 found that leisure-time PA was inversely associated with the risk of PTB, but commuting PA appeared to be positively related to the risk.…”
mentioning
confidence: 99%
“…19, 20 However, individual studies report widely varying results, with relative risks ranging from 0.7 to 5.6 for night or rotating shift work, possibly due to inconsistent definitions of work schedule and insufficient sample sizes in the night or shift work categories. 24, 26, 27, 29, 33, 34, 35 …”
Section: Commentmentioning
confidence: 99%
“…However, research specifically focused on the relationship between walking for a purpose and preterm birth in African-American women is limited and the results are inconclusive. In a prior study of low income African-American women in Baltimore, the researchers found an increased odds of preterm birth for women who walked for a purpose four days or more per week (Misra, Strobino, Stashinko, Nagey, & Nanda, 1998). In contrast, another study in the same city (different institution) reported that African-American women who walked for a purpose for more than 30 minutes per day during pregnancy had lower risk of preterm birth (Sealy-Jefferson, Hegner, & Misra, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, another study in the same city (different institution) reported that African-American women who walked for a purpose for more than 30 minutes per day during pregnancy had lower risk of preterm birth (Sealy-Jefferson, Hegner, & Misra, 2014). Misra and associates (1998) defined walking for a purpose as the average number of days per week in the first and second trimesters combined that a woman spent walking for a purpose and did not collect duration of walking for a purpose (i.e., minutes per day). In contrast, Sealy-Jefferson and colleagues (2014) asked open-ended questions about the duration of walking for a purpose (minutes per day) which may have decreased recall bias.…”
Section: Introductionmentioning
confidence: 99%